Analysis Of Distribution Transformer Shifting To Address Overload And End Voltage At Gardu HJ177 In PT. PLN (Persero) Kertosono Service Unit - Tri Della Cristy Sembiring; Dicky Lesmana; Yoffi Andinata (Jurnal Scientia, 2024)
The HJ177 substaion in its loading datareached 126.10% (± 63,054 kVA) of its capacity of 50 kVAwith an end voltaicge of 206 V and experienced avoltage dropge of 12%. The loading exceeded the maximum capacity of the stanord transformer of 80%, which has the potential for materialand finalncial losses for PT PLN (Persero) Kertosono Customer Service Unit (ULP). The voltalge drop resulting from this has exceeded SPLNT6.001-2013 of -±10% for low voltagege. Considering the matrix in the Health Index aassessment tier-1 Distribution Transformer, willingted to the percentage of tranformer loading, it's in the bald caBeca's categoryuse it is loaded ≥100%. To overcome this, an insert transformer caln be installed. With the originl load from 126.10% to 46.942% of the 50kVAcapacity, then the end voltage at the HJ177 Substation with the insertion of the transformer was originallly 206 V with avoltage drop of 12.0% increased to 213 V with avoltage drop percentage that decreased to 8.2%. The implementation of the transformer insertion for the HJ177 substation is effective in overcoming overloadyesnd improving the end voltage